Supremachist Constructions of Gender in Multiplatform Fictional Narrations and Patriarchal Statism: From conceptual representation to socio-political projection (2023)
Is male ‘supremachism’ really over? The pages you are holding in your hands sow doubts on the common belief that the governance of ‘the macho’ came to its end. As the proverb confirms, ‘the old dies hard’, despite the yet-to-improve individual and institutional efforts to achieve gender equality. With the serious tone this capital issue requires, the author debunks the myth of male supremacism as a phenomenon from a past and raises awareness of the subliminal survival of the supremachist ideological apparatus. Subtlety reveals as a key factor for the survival of subliminal supremachist campaigns, which threatens a promising future of non-discrimination. Essentially, democratic citizenship must pose itself a crucial question: Are current Western societies’ concessions to feminism genuine or a cover by supremachism to survive in an ideologically volatile world?¿Se ha acabado realmente el supremacismo masculino? Estas páginas siembran dudas sobre la opinión común de que el gobierno de “los machos” ha llegado a su fin. Como afirma el proverbio, ‘the old dies hard’, a pesar de los esfuerzos individuales e institucionales para lograr la igualdad de género. La autora desmonta el mito del supremacismo masculino como un fenómeno del pasado y alerta de la pervivencia subliminal del aparato ideológico supremacista. La sutileza se revela como un factor clave para la supervivencia de las campañas subliminales supremacistas, que amenazan un prometedor futuro de no discriminación. Debido a la importancia que tiene este tema, la ciudadanía democrática debe plantearse una pregunta crucial: ¿Las actuales concesiones de las sociedades occidentales al feminismo son auténticas o una tapadera del supremacismo para sobrevivir en un mundo ideológicamente volátil?
Keywords: Desigualdad; género; construcción narrativa; estatismo; conceptualización; alteridad; supremachismo